Computational fluid dynamics (CFD) simulations on gas turbine combustion chamber - Mohd Ikhwan Saifulizam, Roslan (2007)
On a gas turbine engine, the combustion chamber is one of the most important parts to complete the cycle of Brayton. Combustion chamber is used to burn fuel-air mixture to produce energy. This energy are then supply to enter the nozzle and then into the turbine. It is of interest to examine briefly relationship between gas generator speed (Ngg) and efficiencies and also the condition of fuel-air mixture during the combustion. The project needs considerations that dictate the basic geometry of the "conventional" gas turbine combustor. It is also instructive because it helps to define the essential components needed to carry out the primary functions of a combustion chamber. For further step of the project after conducting some experiments, the effort was continued using Computational Fluid Dynamics (CFD) Simulation. The software used was COSMOSFioworks. it was used to observe the flow of the fuel-air mixture during combustion process. There were several factors that affect the level of the efficiency instead of fuel-air mixture ratio that is swirl effect. In the combustion chamber that was being analyzed there was a liner wall with holes drilled around the body to create recirculation (swirl) flow. This factor is also affects the efficiency of the combustion process. Through simulation, the pattern of the flow was observed. The result of the simulation is useful for the design of the combustion chamber and it is useful for further project in order to improve the efficiency of the combustion process.